Plastic deformation of anterior cruciate ligament: listen to the patient, do not just rely on imaging - Sérgio Rocha Piedade; Daniel Miranda Ferreira; Carlos Górios; Nicola Maffulli (Journal of Orthopaedic Surgery and Research)
Abstract Purpose Diagnosing plastic deformation of the anterior cruciate ligament (ACL) is challenging: patients may not report knee instability, and MRI may not confirm the lesion, delaying adequate treatment. This study analyzed clinical findings and complaints in patients with a confirmed diagnosis of plastic deformation of the ACL. Methods Data on complaints, physical, imaging and arthroscopic assessment, and subjective evaluation of 15 patients with undiagnosed or delayed ACL insufficiency from plastic deformation of the ACL (Group 1) and 30 patients who underwent an ACL reconstruction following complete tear of the ACL diagnosed clinically and at imaging (Group 2) were compared and analyzed. Results A knee effusion was reported in both study groups, occurring within the first 4 h after the index knee injury, and it was statistically more significant in the complete ACL tear group. All patients reported low values (zero, one, and two) on a scale from zero to 10 in their confidence in performing high-intensity pivoting sports and physical activities. All patients reported that they did not feel comfortable in performing changing direction pivoting on their injured knee. Conclusion Plastic deformation of the ACL may not be clearly manifest clinically and on MRI, and physical exam may present subtle findings that do not allow to fully assess the function of the injured ligament. Therefore, surgeons should listen to the patient, not just rely on imaging, taking into account the patient's report of how the knee is working and their complaints as they remain the leading guide for decision-making. Level of Evidence IV Diagnostic studies – Investigating a diagnostic test.